Citizens' preferences for a tax exemption for caregivers in inheritance taxation: An empirical analysis using German survey data - Ivo Bischoff; Nataliya Kusa (Philipps-University Marburg, School of Business and Economics, 2017)
We analyze survey data on the proposal to introduce a tax exemption for caregiving heirs to the German inheritance tax. Some 80 percent of the participants support this exemption. We explain interpersonal differences in the support for this tax exemption using a wide range of personal characteristics, beliefs and attitudes. We find self-interest to be relevant: Subjects with alive parents are more likely to support the tax exemption. The same holds for subjects who have personal experience in long- term care provision. While women are at the heart of intergenerational exchange relations, their support for the tax exemption is not found to be higher than for men. Subjects are more likely to support the tax exemption if they adhere to the social norm of indirect reciprocity or overestimate the tax burden of the German inheritance tax.
Keywords: H27; D31; D72; 330; inheritance taxation; long-term care; intergenerational transfers; citizens' pref-erences